Favorable Marker Alleles for Panicle Exsertion Length in Rice (Oryza sativa L.) Mined by Association Mapping and the RSTEP-LRT Method - Dang, Xiaojing; Fang, Bingjie; Chen, Xiangong; Li, Dalu; Sowadan, Ognigamal; Dong, Zhiyao; Liu, Erbao; She, Dong; Wu, Guocan; Liang, Yinfeng; Hong, Delin (Frontiers in Plant Science, 2017)
The panicle exsertion length (PEL) in rice (Oryza sativa L.) is an important trait for hybrid seed production. We investigated the PEL in a chromosome segment substitution line (CSSL) population consisting of 66 lines and a natural population composed of 540 varieties. In the CSSL population, a total of 7 QTLs for PEL were detected across two environments. The percentage of phenotypic variance explained (PVE) ranged from 10.22% to 50.18%, and the additive effect ranged from -1.77 cm to 6.47 cm. Among the 7 QTLs, qPEL10.2 had the largest PVE, 44.05% and 50.18%, with an additive effect of 5.91 cm and 6.47 cm in 2015 and in 2016, respectively. In the natural population, thirteen SSR marker loci were detected that were associated with PEL in all 4 environments, with the PVE ranging from 1.20% to 6.26%. Among the 13 loci, seven were novel. The RM5746-170 bp allele had the largest phenotypic effect (5.11 cm), and the typical carrier variety was Qiaobinghuang. An RM5620-RM6100 region harboring the EUI2 locus on chromosome 10 was detected in both populations. The sequencing results showed that the accessions with a shorter PEL contained the A base, while the accessions with a longer PEL contained the G base at the 1475 bp location of the EUI2 gene.